Application of SSR markers to differentiate new varieties of soybean (Glycine max (L.) Merr.) - Л. М. Присяжнюк; С. І. Мельник; Ю. В. Шитікова; І. О. Сігалова; А. П. Іваницька (Plant Varieties Studying and Protection)
Purpose. To study the molecular genetic polymorphism in new soybean varieties using SSR-markers as for the possibility to apply it for examination of varieties for difference, uniformity and stability.